Optogenetic dissection of basolateral amygdala projections during cue-induced reinstatement of cocaine seeking - Stefanik, Michael T.; Kalivas, Peter W. (Frontiers in Behavioral Neuroscience, 2013)
Stimuli previously associated with drugs of abuse can become triggers that elicit craving and lead to drug-seeking behavior. The basolateral amygdala (BLA) is a key neural structure involved in cue-induced reinstatement of cocaine seeking. Previous studies have also implicated projections from the BLA directly to the nucleus accumbens (NAc) in these behaviors. However, other structures critically involved in cocaine seeking are targets of BLA innervation, including the prelimbic prefrontal cortex (PL). It has been shown that BLA or PL innervation direct to the NAc can modulate reward-related behaviors but the BLA also projects to the PL, and given the importance of the PL projection to the NAc for reinstated drug seeking, we hypothesized the BLA to PL projection may indirectly influence behavior via PL innervation to the NAc. We delivered a virus expressing the inhibitory optogenetic construct ArchT into the BLA and implanted fiber optics above the injection site or axon terminal fields in either the NAc or PL. Rats then went through 12 days of cocaine self-administration followed by extinction training. Following extinction, animals underwent cue-induced reinstatement sessions in the presence or absence of optical inhibition. Inactivation of the BLA and either the BLA core subcompartment of the NAc (BLA-to-NAcore) BLA-to-PL projections inhibited cue-induced reinstatement. These data demonstrate that the BLA projection either directly into the NAc, or indirectly via the PL, is a necessary regulator of drug-seeking behavior.